Upper respiratory microbiome composition and associations with air pollution and infant respiratory health: a longitudinal study in Guatemala - Rina Das; Andrew Baldi; Sant-Rayn Pasricha; Lisa M. Thompson; Anaité Díaz-Artiga; Laura Maria Grajeda; John P. McCracken; Kelsey Jesser; Lance Waller; Matthew C. Freeman; Thomas Clasen; Sheela S. Sinharoy (International Journal of Hygiene and Environmental Health, 2026)

Multi-media occurrence, bioaccumulation, and exposure assessment of PFAS across a Midwestern U.S. State - Maria S. Sepúlveda; Lisa Brown; Staci L. Capozzi; Samantha C. Cullom; Jeffrey E. Dick; Daniel J. Foti; Ronaldo H. Franjul; Nicole L. Franklin; Jennifer L. Freeman; Carolina Gonzalez-Canas; Wanyue Hui; Yuxin Jiang; et al. (Environmental Research, 2026)

Restoration of ecological interactions: The influence of site and landscape factors - B.A. Woodcock; E. Waddell; M.G. Weites; M. Guy; M. Freeman; K. Park; E. Fuentes-Montemayor; K. Watts; R.J. Barnett; S. l. Rogerson; A. Opris; J. Harris; et al. (Agriculture, Ecosystems & Environment, 2026)

Evidence for Widespread Inter‐Basin Vicariance of Fishes Associated With Quiescent Geologic Features in the Southeastern United States - Bryson G. Hilburn; Byron J. Freeman; Eric J. Walther; Mary C. Freeman; David S. Leigh; John P. Wares (Journal of Biogeography, 2026)
Aim Stream captures are implicated as drivers of speciation in many groups of lotic fishes. In the southeastern United States, numerous stream‐dwelling animals possess restricted trans‐divide populations at localities where quiescent geologic features intersect drainage divides, suggesting potential evidence for inter‐basin vicariance via stream capture. However, there has not yet been a comprehensive quantitative biogeographical analysis of these patterns. Herein, we present evidence for widespread patterns of evolutionarily recent inter‐basin vicariant events across major geologic structures that have been tectonically dormant for many millions of years. Location Southeastern North America. Taxon Freshwater fishes. Methods We used Kriging spatial interpolation analysis on a dataset of 5434 sample sites (~188,000 species‐specific distribution records) that included ~375 fish species to visualise patterns of aberrant fish distribution records across highland physiographic regions of Alabama, Georgia, Tennessee, and the Carolinas (USA). These patterns were further explored with a comprehensive synthesis of published fish distribution maps and museum records. We collected cytochrome‐ b sequence data from 337 individual fish of 14 representative ‘transferred’ species (20 intraspecies population pairs) from ~11 paired localities across the Brevard Fault, Allatoona Fault, and Blue Ridge Escarpment implicated in inter‐basin captures to estimate coarse timing of vicariant events and to infer distributional artefacts caused by anthropogenic introduction. Results A heatmap generated from Kriging analysis shows a concentration of aberrant distributional records of fishes around the Brevard Fault Zone and the Blue Ridge Escarpment and other more minor quiescent geologic features. Our synthesis of museum records and fish distribution literature revealed documented evidence of a total of 115 species‐transfer incidences (52 taxa) that exhibit inter‐basin transfer along these features. Of the 20 intraspecies population pairs examined for genetic diversity, measures of Φ ST and associated AMOVA p ‐values indicate significant levels of genetic divergence for 13. Main Conclusions Large‐scale, quiescent geologic structures appear to drive localised vicariant events via stream capture through fostering differential erosional rates of captor and victim tributaries. Stream capture emerges as a prevalent process underlying inter‐basin range expansion and diversification of aquatic animals in upland regions.

Effect of water, sanitation, and hygiene on childhood growth in Ethiopia: a cluster-randomized trial - Tahvi Frank; Isabel J.B. Thompson; Solomon Aragie; Dionna M. Wittberg; Wondyifraw Tadesse; Adane Dagnew; Dagnachew Hailu; Jason S. Melo; Taye Zeru; Zerihun Tadesse; Benjamin F. Arnold; Matthew C. Freeman; et al. (International Journal of Hygiene and Environmental Health, 2026)

P28-35 Xylene: weight of evidence approach case study to determine the need for an extended one generation reproductive study with a developmental neurotoxicity animal cohort - L. Higgins; C. Haines; F. Faulhammer; M. Rooseboom; N. Aygun Kocabas; J.H. Arts; A. Cordova; E. Freeman; M. Nahar; E. Richmond; S. Schneider; K. Morris-Schaffer (Toxicology Letters, 2025)

Carbaryl use and incident cancer in the Agricultural Health Study: an updated analysis - Patricia A. Erickson; Gabriella Andreotti; Richard V. Remigio; Mary H. Ward; Christine G. Parks; Dale P. Sandler; Paul S. Albert; Kathryn Hughes Barry; Jonathan N. Hofmann; Laura E. Beane Freeman (International Journal of Hygiene and Environmental Health, 2025)

Metabolic gene expression differences in emaciated and moderately conditioned horses: RNA-seq analysis of postmortem skeletal muscle - M. Parr; E. Shepherd; M. Hines; L. Strickland; T. Freeman; S. Moisa; J. Beever; J. Ivey (Journal of Equine Veterinary Science, 2025)

Genetic variants of vitamin D, estrogen α, parathyroid and collagen type I alpha receptor gene and its influence on circulating serum osteocalcin in postmenopausal osteoporosis: A cohort study - Chrisanne Freeman; Jebasingh Tennyson; A. S. Priscilla (The Nucleus, 2025)

Corrigendum to “Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes” [Biol. Conserv. 300 (2024), 110843] - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2025)

Accumulation of microbial hazards and assessment of food hygiene associated with broiler chicken processing at open air food markets in Maputo, Mozambique - Frederica Lamar; Amélia Mondlane-Milisse; Denise R.A. Brito; Hermógenes N. Mucache; Kelsey J. Jesser; Christine S. Fagnant-Sperati; Courtney Victor; Kayoko Shioda; José M. Fafetine; Joaquim Ângelo Osvaldo Saíde; Eric M. Fèvre; Mia Catharine Mattioli; et al. (International Journal of Food Microbiology, 2025)

Troubled waters in the land down under: Pervasive threats and high extinction risks demand urgent conservation actions to protect Australia's native freshwater fishes - Mark Lintermans; Maiko Lutz; Nick S. Whiterod; Bernd Gruber; Michael P. Hammer; Mark J. Kennard; David L. Morgan; Tarmo A. Raadik; Peter Unmack; Steven Brooks; Brendan C. Ebner; Dean Gilligan; et al. (Biological Conservation, 2024)

Unraveling the Intricacies of OPG/RANKL/RANK Biology and Its Implications in Neurological Disorders—A Comprehensive Literature Review - Chrisanne Freeman; Merlyn Diana A. S; Priscilla A. S (Molecular Neurobiology, 2024)

Review of skeletal carbonate mineralogy of brachiopods with new material from New Zealand - Abigail M. Smith; David F. Freeman; Ian S. Dixon‐Anderson; Daphne E. Lee (New Zealand Journal of Marine and Freshwater Research, 2024)
We combine published and new mineralogical data on most major taxa of brachiopods from all over the world, to investigate patterns and controls on brachiopod carbonate mineralogy. Measurements of 1726 specimens in 162 species (including 56 fossil species) ranged from 79°N to 74°S and from intertidal to almost 4000 m deep. Calcareous brachiopods mostly create strong resilient valves of very low‐Mg calcite ( = 1.3 wt% MgCO 3 ). The substrate‐cemented Craniida ( = 8.9 wt% MgCO 3 ) and Thecideida ( = 6.5 wt% MgCO 3 ) are unusual in precipitating calcite with higher Mg content. This is the first study to find bimineralic brachiopods; a few species show a combination of low‐Mg ( = 0.8 wt% MgCO 3 ) and intermediate‐Mg calcite ( = 7.2 wt% MgCO 3 ) ( sensu Smith AM, Key MM Jr, Gordon DP. 2006. Skeletal mineralogy of bryozoans: taxonomic and temporal patterns. Earth‐Science Reviews. 78:287–306.). While Mg in calcite varies systematically among valve layers and sometimes along the growth axis, we found no consistent difference between valves of the same individual. A weak latitudinal signal indicates some overall temperature control of Mg, but in general, brachiopods are active calcifiers, precipitating low‐Mg calcite even when Mg:Ca ratio in seawater is high. The drivers on brachiopod mineralogy are individual, environmental, and phylogenetic – resulting in complex variability.

The natural anthraquinone dye emodin: Eco/genotoxicological characterization for aquatic organisms - Natália Oliveira de Farias; Amanda Rocha Rodrigues; Marina Tenório Botelho; Gabriel Rampazzo Magalhães; Riikka Räisänen; Harold S. Freeman; Gisela de Aragão Umbuzeiro (Food and Chemical Toxicology, 2024)

Benign breast disease and breast cancer risk in African women: a case–control study - Olasubomi J. Omoleye; Jincong Q. Freeman; Mojisola Oluwasanu; Adenike Adeniji-Sofoluwe; Anna E. Woodard; Benjamin S. Aribisala; Prisca O. Adejumo; Atara Ntekim; Timothy Makumbi; Paul Ndom; IkeOluwapo O. Ajayi; Olufunmilayo I. Olopade; et al. (Cancer Causes & Control, 2024)

A study of an interstellar object explorer (IOE) mission - S. Alan Stern; Silvia Protopapa; Matthew Freeman; Joel Wm. Parker; Mark Tapley; Darryl Z. Seligman; Caden Andersson (Planetary and Space Science, 2024)

Characterization of novel mouse models to study the role of necroptosis in aging and age-related diseases - Ramasamy Selvarani; Hoang Van Michelle Nguyen; Nidheesh Thadathil; Roman F. Wolf; Willard M. Freeman; Christopher D. Wiley; Sathyaseelan S. Deepa; Arlan Richardson (GeroScience, 2023)
To study the impact of necroptosis-induced chronic inflammation on age-related diseases and aging, two knockin mouse models ( Ripk3 -KI and Mlkl -KI) were generated that overexpress two genes involved in necroptosis ( Ripk3 or Mlkl ) when crossed to Cre transgenic mice. Crossing Ripk3 -KI or Mlkl -KI mice to albumin-Cre transgenic mice produced hepatocyte specific hRipk3 -KI or hMlkl -KI mice, which express the two transgenes only in the liver. Ripk3 and Mlkl proteins were overexpressed 10- and fourfold, respectively, in the livers of the hRipk3 -KI or hMlkl -KI mice. Treating young (2-month) hRipk3 -KI or hMlkl -KI mice with carbon tetrachloride (CCl 4 ), a chemical inducer of oxidative stress, resulted in increased necroptosis (Mlkl-oligomers) and inflammation in the liver compared to control mice receiving CCl 4 . Mlkl-oligomerization also was significantly increased in old (18-month) hRipk3 -KI and hMlkl -KI mice compared to old control (Cre negative, Ripk3 -KI and Mlkl -KI) mice. The increase in necroptosis was associated with an increase in inflammation, e.g., inflammatory cytokines (TNFα, IL-6) and macrophage markers (F4/80, CD68). Importantly, steatosis (triglycerides) and fibrosis (e.g., picrosirius red staining, hydroxyproline levels, and transcripts for TGFβ, Col1α1, and Col3α1) that increase with age were significantly higher in the livers of the old hRipk3 -KI or hMlkl -KI mice compared to old control mice. In addition, markers of cellular senescence were significantly increased in the livers of the old hRipk3 -KI and hMlkl -KI mice. Thus, the first mouse models have been developed that allow researchers to study the impact of inducing necroptosis in specific cells/tissues on chronic inflammation in aging and age-related diseases.

Choice between food and cocaine or fentanyl reinforcers under fixed and variable schedules in female and male rhesus monkeys - W. S. Doyle; K. B. Freeman; J. Woods; S. L. Huskinson (Psychopharmacology, 2023)

The Use of Collagen Methacrylate in Actuating Polyethylene Glycol Diacrylate–Acrylic Acid Scaffolds for Muscle Regeneration - Yoliem S. Miranda Alarcón; Dorota Jazwinska; Terrence Lymon; Amin Khalili; Daniel Browe; Brandon Newton; Michael Pellegrini; Rick I. Cohen; David I. Shreiber; Joseph W. Freeman (Annals of Biomedical Engineering, 2023)

25 The potential impact of female body shape on rider posture and scores received from dressage judges - S. Forino; L. Cameron; N. Stones; V. Lewis; F. Freeman (Journal of Equine Veterinary Science, 2023)

A rapid assessment technique for evaluating biodiversity to support accreditation of residential properties - Y. van Heezik; B.I.P. Barratt; B.R. Burns; B.D. Clarkson; B.T. Cutting; R. Ewans; C. Freeman; C. Meurk; D.F. Shanahan; R. Simcock; G. Souter-Brown; M.C. Stanley; et al. (Landscape and Urban Planning, 2023)

Correction to: Clinical trial-ready patient cohorts for multiple system atrophy: coupling biospecimen and iPSC banking to longitudinal deep-phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Ashlan S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)

Genetic variation in fire recovery and other fire-related traits in a global eucalypt species - Mariano A. Hernández; Jakob B. Butler; Hans Ammitzboll; Jules S. Freeman; Julianne O’Reilly-Wapstra; René E. Vaillancourt; Brad M. Potts (Tree Genetics & Genomes, 2022)
To understand the potential of forests to adapt to wildfire, we studied the genetic architecture of fire-related structural, damage and recovery traits in a globally important Australian forest tree species, Eucalyptus globulus . Fourteen traits were evaluated in an outcrossed F 2 population in a field trial in Tasmania, Australia, which was burnt by a wildfire 14 years after planting. The trial also included open-pollinated families of the grandparental dwarf and tall ecotypes used to produce the F 2 population. We studied the phenotypic correlations within the F 2 population and performed quantitative trait loci (QTL) analyses using a linkage map comprised of 472 markers. Ecotype comparisons revealed that almost all traits were under genetic control, with trees of the dwarf ecotype significantly more damaged and mainly recovering from lignotubers, whereas tall ecotype trees mainly recovered from epicormic resprouts extending for a variable height up the stem. Within the F 2 , tree size was negatively correlated with fire damage and positively correlated with recovery. Genetic control of fire-related traits was confirmed by the detection of 38 QTL in the F 2 population. These QTL accounted for 4 to 43% of the phenotypic variation in these traits. Several QTL co-located and likely reflect pleiotropic effects. However, many independent QTL were detected, including QTL for crown consumption and trunk scorch, epicormic resprouting, resprout herbivory, and seedling establishment. The QTL detected argue that many genetically controlled mechanisms are responsible for variation in fire damage and recovery.

Clinical Trial-Ready Patient Cohorts for Multiple System Atrophy: Coupling Biospecimen and iPSC Banking to Longitudinal Deep-Phenotyping - Alain Ndayisaba; Ariana T. Pitaro; Andrew S. Willett; Kristie A. Jones; Claudio Melo de Gusmao; Abby L. Olsen; Jisoo Kim; Eero Rissanen; Jared K. Woods; Sharan R. Srinivasan; Anna Nagy; Amanda Nagy; et al. (The Cerebellum, 2022)
Multiple system atrophy (MSA) is a fatal neurodegenerative disease of unknown etiology characterized by widespread aggregation of the protein alpha-synuclein in neurons and glia. Its orphan status, biological relationship to Parkinson’s disease (PD), and rapid progression have sparked interest in drug development. One significant obstacle to therapeutics is disease heterogeneity. Here, we share our process of developing a clinical trial-ready cohort of MSA patients (69 patients in 2 years) within an outpatient clinical setting, and recruiting 20 of these patients into a longitudinal “n-of-few” clinical trial paradigm. First, we deeply phenotype our patients with clinical scales (UMSARS, BARS, MoCA, NMSS, and UPSIT) and tests designed to establish early differential diagnosis (including volumetric MRI, FDG-PET, MIBG scan, polysomnography, genetic testing, autonomic function tests, skin biopsy) or disease activity (PBR06-TSPO). Second, we longitudinally collect biospecimens (blood, CSF, stool) and clinical, biometric, and imaging data to generate antecedent disease-progression scores. Third, in our Mass General Brigham SCiN study ( s tem c ells i n n eurodegeneration), we generate induced pluripotent stem cell (iPSC) models from our patients, matched to biospecimens, including postmortem brain. We present 38 iPSC lines derived from MSA patients and relevant disease controls (spinocerebellar ataxia and PD, including alpha-synuclein triplication cases), 22 matched to whole-genome sequenced postmortem brain. iPSC models may facilitate matching patients to appropriate therapies, particularly in heterogeneous diseases for which patient-specific biology may elude animal models. We anticipate that deeply phenotyped and genotyped patient cohorts matched to cellular models will increase the likelihood of success in clinical trials for MSA.

Copaifera langsdorffii Desf. bark extract: optimisation of dyeing conditions to wool and colour fastness properties - Patricia Muniz dos Santos Silva; Vitória Hamawaki França; Rayana Santiago de Queiroz; Fernando Soares de Lima; Harold S. Freeman; Silgia Aparecida da Costa; Sirlene Maria da Costa (Natural Product Research, 2022)

Correction to: The CannTeen study: verbal episodic memory, spatial working memory, and response inhibition in adolescent and adult cannabis users and age‑matched controls - W. Lawn; N. Fernandez‑Vinson; C. Mokrysz; G. Hogg; R. Lees; K. Trinci; K. Petrilli; A. Borissova; S. Ofori; S. Waters; P. Michór; M. B. Wall; et al. (Psychopharmacology, 2022)

Charcoal rot (Macrophomina phaseolina) across melon diversity: evaluating the interaction between the pathogen, plant age and environmental conditions as a step towards breeding for resistance - Roni Cohen; Meital Elkabetz; Harry S. Paris; Stanley Freeman; Amit Gur (European Journal of Plant Pathology, 2022)

Patterns of genomic diversity and linkage disequilibrium across the disjunct range of the Australian forest tree Eucalyptus globulus - Jakob B. Butler; Jules S. Freeman; Brad M. Potts; René E. Vaillancourt; Hossein V. Kahrood; Peter K. Ades; Philippe Rigault; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2022)
The evolutionary trajectory of a population both influences and is influenced by characteristics of its genome. A disjunct population, for example is likely to exhibit genomic features distinct from those of continuous populations, reflecting its specific evolutionary history and influencing future recombination outcomes. We examined genetic diversity, population differentiation and linkage disequilibrium (LD) across the highly disjunct native range of the Australian forest tree Eucalyptus globulus , using 203,337 SNPs genotyped in 136 trees spanning seven races. We found support for four broad genetic groups, with moderate F ST , high allelic diversity and genome-wide LD decaying to an r 2 of 0.2 within 4 kb on average. These results are broadly similar to those reported previously in Eucalyptus species and support the ‘ring’ model of migration proposed for E. globulus . However, two of the races (Otways and South-eastern Tasmania) exhibited a much slower decay of LD with physical distance than the others and were also the most differentiated and least diverse, which may reflect the effects of selective sweeps and/or genetic bottlenecks experienced in their evolutionary history. We also show that F ST and rates of LD vary within and between chromosomes across all races, suggestive of recombination outcomes influenced by genomic features, hybridization or selection. The results obtained from studying this species serve to illustrate the genomic effects of population disjunction and further contribute to the characterisation of genomes of woody genera.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Responsible agriculture must adapt to the wetland character of mid‐latitude peatlands - Benjamin W. J. Freeman; Chris D. Evans; Samuel Musarika; Ross Morrison; Thomas R. Newman; Susan E. Page; Giles F. S. Wiggs; Nicholle G. A. Bell; David Styles; Yuan Wen; David R. Chadwick; Davey L. Jones (Global Change Biology, 2022)
Drained, lowland agricultural peatlands are greenhouse gas (GHG) emission hotspots and a large but vulnerable store of irrecoverable carbon. They exhibit soil loss rates of ~2.0 cm yr −1 and are estimated to account for 32% of global cropland emissions while producing only 1.1% of crop kilocalories. Carbon dioxide emissions account for >80% of their terrestrial GHG emissions and are largely controlled by water table depth. Reducing drainage depths is, therefore, essential for responsible peatland management. Peatland restoration can substantially reduce emissions. However, this may conflict with societal needs to maintain productive use, to protect food security and livelihoods. Wetland agriculture strategies will, therefore, be required to adapt agriculture to the wetland character of peatlands, and balance GHG mitigation against productivity, where halting emissions is not immediately possible. Paludiculture may substantially reduce GHG emissions but will not always be viable in the current economic landscape. Reduced drainage intensity systems may deliver partial reductions in the rate of emissions, with smaller modifications to existing systems. These compromise systems may face fewer hurdles to adoption and minimize environmental harm until societal conditions favour strategies that can halt emissions. Wetland agriculture will face agronomic, socio‐economic and water management challenges, and careful implementation will be required. Diversity of values and priorities among stakeholders creates the potential for conflict. Successful implementation will require participatory research approaches and co‐creation of workable solutions. Policymakers, private sector funders and researchers have key roles to play but adoption risks would fall predominantly on land managers. Development of a robust wetland agriculture paradigm is essential to deliver resilient production systems and wider environmental benefits. The challenge of responsible use presents an opportunity to rethink peatland management and create thriving, innovative and green wetland landscapes for everyone's future benefit, while making a vital contribution to global climate change mitigation.

Future climate risks from stress, insects and fire across US forests - William R. L. Anderegg; Oriana S. Chegwidden; Grayson Badgley; Anna T. Trugman; Danny Cullenward; John T. Abatzoglou; Jeffrey A. Hicke; Jeremy Freeman; Joseph J. Hamman (Ecology Letters, 2022)
Forests are currently a substantial carbon sink globally. Many climate change mitigation strategies leverage forest preservation and expansion, but rely on forests storing carbon for decades to centuries. Yet climate‐driven disturbances pose critical risks to the long‐term stability of forest carbon. We quantify the climate drivers that influence wildfire and climate stress‐driven tree mortality, including a separate insect‐driven tree mortality, for the contiguous United States for current (1984–2018) and project these future disturbance risks over the 21st century. We find that current risks are widespread and projected to increase across different emissions scenarios by a factor of >4 for fire and >1.3 for climate‐stress mortality. These forest disturbance risks highlight pervasive climate‐sensitive disturbance impacts on US forests and raise questions about the risk management approach taken by forest carbon offset policies. Our results provide US‐wide risk maps of key climate‐sensitive disturbances for improving carbon cycle modeling, conservation and climate policy.

The CannTeen study: verbal episodic memory, spatial working memory, and response inhibition in adolescent and adult cannabis users and age-matched controls - W. Lawn; N. Fernandez-Vinson; C. Mokrysz; G. Hogg; R. Lees; K. Trinci; K. Petrilli; A. Borissova; S. Ofori; S. Waters; P. Michór; M. B. Wall; et al. (Psychopharmacology, 2022)
Background Preclinical and human studies suggest that adolescent cannabis use may be associated with worse cognitive outcomes than adult cannabis use. We investigated the associations between chronic cannabis use and cognitive function in adolescent and adult cannabis users and controls. We hypothesised user-status would be negatively associated with cognitive function and this relationship would be stronger in adolescents than adults. Methods As part of the ‘CannTeen’ project, this cross-sectional study assessed cognitive performance in adolescent cannabis users ( n = 76; 16–17-year-olds), adolescent controls ( n = 63), adult cannabis users ( n = 71; 26–29-year-olds) and adult controls ( n = 64). Users used cannabis 1–7 days/week. Adolescent and adult cannabis users were matched on cannabis use frequency (4 days/week) and time since last use (2.5 days). Verbal episodic memory (VEM) was assessed using the prose recall task, spatial working memory (SWM) was assessed using the spatial n-back task, and response inhibition was assessed with the stop-signal task. Primary outcome variables were: delayed recall, 3-back discriminability, and stop signal reaction time, respectively. Results Users had worse VEM than controls ( F (1,268) = 7.423, p = 0.007). There were no significant differences between user-groups on SWM or response inhibition. Null differences were supported by Bayesian analyses. No significant interactions between age-group and user-group were found for VEM, SWM, or response inhibition. Conclusions Consistent with previous research, there was an association between chronic cannabis use and poorer VEM, but chronic cannabis use was not associated with SWM or response inhibition. We did not find evidence for heightened adolescent vulnerability to cannabis-related cognitive impairment.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Molecular characterization and ecotoxicological evaluation of the natural dye madder and its chlorinated products - Harold S. Freeman; Tuane C. dos Santos; Yufei Chen; Josiane A. S. Vendemiatti; Adria C. de Oliveira; Francine I. Vacchi; Nelson R. Vinueza; Gisela A. Umbuzeiro (Environmental Science and Pollution Research, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Machine Learning Can Assign Geologic Basin to Produced Water Samples Using Major Ion Geochemistry - Jenna L. Shelton; Aaron M. Jubb; Samuel W. Saxe; Emil D. Attanasi; Alexei V. Milkov; Mark Engle; Philip A. Freeman; Christopher A. Shaffer; Madalyn S. Blondes (Natural Resources Research, 2021)
Understanding the geochemistry of waters produced during petroleum extraction is essential to informing the best treatment and reuse options, which can potentially be optimized for a given geologic basin. Here, we used the US Geological Survey’s National Produced Waters Geochemical Database (PWGD) to determine if major ion chemistry could be used to classify accurately a produced water sample to a given geologic basin based on similarities to a given training dataset. Two datasets were derived from the PWGD: one with seven features but more samples (PWGD7), and another with nine features but fewer samples (PWGD9). The seven-feature dataset, prior to randomly generating a training and testing (i.e., validation) dataset, had 58,541 samples, 20 basins, and was classified based on total dissolved solids (TDS), bicarbonate (HCO 3 ), Ca, Na, Cl, Mg, and sulfate (SO 4 ). The nine-feature dataset, prior to randomly splitting into a training and testing (i.e., validation) dataset, contained 33,271 samples, 19 basins, and was classified based on TDS, HCO 3 , Ca, Na, Cl, Mg, SO 4 , pH, and specific gravity. Three supervised machine learning algorithms—Random Forest, k-Nearest Neighbors, and Naïve Bayes—were used to develop multi-class classification models to predict a basin of origin for produced waters using major ion chemistry. After training, the models were tested on three different datasets: Validation7, Validation9, and one based on data absent from the PWGD. Prediction accuracies across the models ranged from 23.5 to 73.5% when tested on the two PWGD-based datasets. A model using the Random Forest algorithm predicted most accurately compared to all other models tested. The models generally predicted basin of origin more accurately on the PWGD7-based dataset than on the PWGD9-based dataset. An additional dataset, which contained data not in the PWGD, was used to test the most accurate model; results suggest that some basins may lack geochemical diversity or may not be well described, while others may be geochemically diverse or are well described. A compelling result of this work is that a produced water basin of origin can be determined using major ions alone and, therefore, deep basinal fluid compositions may not be as variable within a given basin as previously thought. Applications include predicting the geochemistry of produced fluid prior to drilling at different intervals and assigning historical produced water data to a producing basin.

Soft-Sediment Communities of the Northern Indian River Lagoon, FL, United States - Jessica Lunt; Christopher J. Freeman; Dean S. Janiak; Katrina Bayliss; Michelle Stephens; Eve Galimany; Valerie J. Paul (Frontiers in Marine Science, 2021)
Understanding the structure and function of infaunal communities is useful in determining the biodiversity and ecosystem function of shallow estuaries. We conducted a survey of infaunal communities within three separate water basins [Mosquito Lagoon (ML), Indian River (IR), and Banana River (BR)] in the larger Northern Indian River Lagoon, FL, United States to establish a database of infaunal community structure and function. Twenty-seven sites were sampled quarterly from 2014 to 2016. Analysis of all samples determined that basin, season, and sediment composition were the primary drivers of macrobenthic community composition. Diversity was highest in the ML, and lower in spring compared to other seasons. The occurrence of a brown tide ( Aureoumbra lagunensis ) in 2016 allowed a comparison of winter and spring communities before (2015) and during (2016) a bloom event. Community composition and diversity at the BR sites were the most affected by the bloom event with the lowest diversity and abundances during the bloom. Diversity in the IR was also lower during the bloom, while the ML was unaffected by the bloom. Species of all feeding groups were affected by the bloom, with lower abundances found in all groups. In addition, to determine the overall trophic diversity of infaunal communities, we collected infaunal organisms from two of the quarterly sampled sites for isotope analyses. Values of δ 13 C and δ 15 N from infaunal tissue were compared to those of potential food sources at each site. Substantial interspecific variation in isotope values of infaunal organisms within a site suggests the presence of diverse nutritional modes that include suspension and deposit feeding and predation. Together, these data suggest that infaunal communities contribute to benthic pelagic coupling and nutrient cycling within the estuarine communities, but the overall function of these communities may be tightly linked to their species composition.

Multiscale Digital Rock Analysis for Complex Rocks - L. C. Ruspini; P. E. Øren; S. Berg; S. Masalmeh; T. Bultreys; C. Taberner; T. Sorop; F. Marcelis; M. Appel; J. Freeman; O. B. Wilson (Transport in Porous Media, 2021)

Assessing awareness on biodiversity conservation among Nigerians: the Aichi Biodiversity Target 1 - Emmanuel O. Akindele; Michael C. Ekwemuka; Paul Apeverga; Tajudeen O. Amusa; Samuel Olajuyigbe; Oluwakayode M. Coker; Fatsuma Olaleru; Michelle Fasona; Elizabeth N. Usen; Abubakar S. Ringim; Opeyemi A. Adedoja; Chinedu C. Nsude; et al. (Biodiversity and Conservation, 2021)

Climate change impacts on human health at an actionable scale: a state-level assessment of Indiana, USA - G. M. Filippelli; J. L. Freeman; J. Gibson; S. Jay; M. J. Moreno-Madriñán; I. Ogashawara; F. S. Rosenthal; Y. Wang; E. Wells (Climatic Change, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Adaptations for amphibious vision in sea otters (Enhydra lutris): structural and functional observations - Sarah McKay Strobel; Bret A. Moore; Kate S. Freeman; Michael J. Murray; Colleen Reichmuth (Journal of Comparative Physiology A, 2020)

Quantification of observable behaviors induced by typical and atypical kappa-opioid receptor agonists in male rhesus monkeys - S. L. Huskinson; D. M. Platt; M. Brasfield; M. E. Follett; T. E. Prisinzano; B. E. Blough; K. B. Freeman (Psychopharmacology, 2020)

Effects of Mowing and Prescribed Fire on Plant Community Structure and Function in Rare Coastal Sandplains, Nantucket Island, MA, USA - Helen Mills Poulos; Rachael S. Freeman; Jennifer M. Karberg; Karen C. Beattie; Danielle I. O’Dell; Kelly A. Omand (Environmental Management, 2020)

A pharmacokinetic-pharmacodynamic assessment of oral antibiotics for pyelonephritis - J. W. S. Cattrall; E. Asín-Prieto; J. Freeman; I. F. Trocóniz; A. Kirby (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Independent QTL underlie resistance to the native pathogen Quambalaria pitereka and the exotic pathogen Austropuccinia psidii in Corymbia - Jakob B. Butler; Brad M. Potts; René E. Vaillancourt; David J. Lee; Geoff S. Pegg; Jules S. Freeman (Tree Genetics & Genomes, 2019)

The Joint IOC (of UNESCO) and WMO Collaborative Effort for Met-Ocean Services - Nadia Pinardi; Johan Stander; David M. Legler; Kevin O'Brien; Tim Boyer; Tom Cuff; Pierre Bahurel; Mathieu Belbeoch; Sergey Belov; Shelby Brunner; Eugene Burger; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Cancer incidence in the Agricultural Health Study after 20 years of follow-up - Catherine C. Lerro; Stella Koutros; Gabriella Andreotti; Dale P. Sandler; Charles F. Lynch; Lydia M. Louis; Aaron Blair; Christine G. Parks; Srishti Shrestha; Jay H. Lubin; Paul S. Albert; Jonathan N. Hofmann; et al. (Cancer Causes & Control, 2019)

Response of cell-wall composition and RNA-seq transcriptome to methyl-jasmonate in Brachypodium distachyon callus - Lucy S. Hyde; Till K. Pellny; Jackie Freeman; Louise V. Michaelson; Rachael Simister; Simon J. McQueen-Mason; Rowan A. C. Mitchell (Planta, 2018)

Dissociable effects of the kappa opioid receptor agonist nalfurafine on pain/itch-stimulated and pain/itch-depressed behaviors in male rats - Matthew L. Lazenka; Megan J. Moerke; E. Andrew Townsend; Kevin B. Freeman; F. Ivy Carroll; S. Stevens Negus (Psychopharmacology, 2018)

A geographic information system-based method for estimating cancer rates in non-census defined geographical areas - Vincent L. Freeman; Emma E. Boylan; Oksana Pugach; Sara L. Mclafferty; Katherine Y. Tossas-Milligan; Karriem S. Watson; Robert A. Winn (Cancer Causes & Control, 2017)

Effects of nalfurafine on the reinforcing, thermal antinociceptive, and respiratory-depressant effects of oxycodone: modeling an abuse-deterrent opioid analgesic in rats - E. Andrew Townsend; Jennifer E. Naylor; S. Stevens Negus; Shelley R. Edwards; Hina N. Qureshi; Hunter W. McLendon; Christopher R. McCurdy; Coco N. Kapanda; Jussara M. do Carmo; Fernanda S. da Silva; John E. Hall; Kenneth J. Sufka; et al. (Psychopharmacology, 2017)

Changes in the US hurricane disaster landscape: the relationship between risk and exposure - Ashley C. Freeman; Walker S. Ashley (Natural Hazards, 2017)

The neuronal metabolite NAA regulates histone H3 methylation in oligodendrocytes and myelin lipid composition - N. K. Singhal; H. Huang; S. Li; R. Clements; J. Gadd; A. Daniels; E. E. Kooijman; P. Bannerman; T. Burns; F. Guo; D. Pleasure; E. Freeman; et al. (Experimental Brain Research, 2017)

Constructed wetlands may lower inorganic nutrient inputs but enhance DOC loadings into a drinking water reservoir in North Wales - C. Scholz; T. G. Jones; M. West; A. M. S. Ehbair; C. Dunn; C. Freeman (Environmental Science and Pollution Research, 2016)

Evidence for different QTL underlying the immune and hypersensitive responses of Eucalyptus globulus to the rust pathogen Puccinia psidii - J. B. Butler; J. S. Freeman; R. E. Vaillancourt; B. M. Potts; M. Glen; D. J. Lee; G. S. Pegg (Tree Genetics & Genomes, 2016)

Application of Effective Discharge Analysis to Environmental Flow Decision-Making - S. Kyle McKay; Mary C. Freeman; Alan P. Covich (Environmental Management, 2016)

Estuarine fouling communities are dominated by nonindigenous species in the presence of an invasive crab - Aaren S. Freeman; Alejandro Frischeisen; April MH. Blakeslee (Biological Invasions, 2016)

An amniote life‐history database to perform comparative analyses with birds, mammals, and reptiles - Nathan P. Myhrvold; Elita Baldridge; Benjamin Chan; Dhileep Sivam; Daniel L. Freeman; S. K. Morgan Ernest (Ecology, 2015)
Studying life‐history traits within and across taxonomic classifications has revealed many interesting and important patterns, but this approach to life history requires access to large compilations of data containing many different life‐history parameters. Currently, life‐history data for amniotes (birds, mammals, and reptiles) are split among a variety of publicly available databases, data tables embedded in individual papers and books, and species‐specific studies by experts. Using data from this wide range of sources is a challenge for conducting macroecological studies because of a lack of standardization in taxonomic classifications, parameter values, and even in which parameters are reported. In order to facilitate comparative analyses between amniote life‐history data, we created a database compiled from peer‐reviewed studies on individual species, macroecological studies of multiple species, existing life‐history databases, and other aggregated sources as well as published books and other compilations. First, we extracted and aggregated the raw data from the aforementioned sources. Next, we resolved spelling errors and other formatting inconsistencies in species names through a number of computational and manual methods. Once this was completed, subspecies‐level data and species‐level data were shared via a data‐sharing algorithm to accommodate the variety of species transformations (taxonomic promotions, demotions, merges, divergences, etc.) that have occurred over time. Finally, in species where multiple raw data points were identified for a given parameter, we report the median value. Here, we report a normalized and consolidated database of up to 29 life‐history parameters, containing at least one life‐history parameter for 21 322 species of birds, mammals, and reptiles.

T-bet and interleukin-27: possible TH1 immunomodulators of sarcoidosis - Wei Sheng Joshua Loke; Araluen Freeman; Linda Garthwaite; Silvie Prazakova; Mijeong Park; Kenneth Hsu; Paul S. Thomas; Cristan Herbert (Inflammopharmacology, 2015)

Comparison of trends in butterfly populations between monitoring schemes - D. B. Roy; E. F. Ploquin; Z. Randle; K. Risely; M. S. Botham; I. Middlebrook; D. Noble; K. Cruickshanks; S. N. Freeman; T. M. Brereton (Journal of Insect Conservation, 2015)

Association mapping for wood quality and growth traits in Eucalyptus globulus ssp. globulus Labill identifies nine stable marker-trait associations for seven traits - Saravanan Thavamanikumar; Luke J. McManus; Peter K. Ades; Gerd Bossinger; Desmond J. Stackpole; Richard Kerr; Sara Hadjigol; Jules S. Freeman; René E. Vaillancourt; Peng Zhu; Josquin F. G. Tibbits (Tree Genetics & Genomes, 2014)

Clostridium difficile as a cause of healthcare-associated diarrhoea among children in Auckland, New Zealand: clinical and molecular epidemiology - V. Sathyendran; G. N. McAuliffe; T. Swager; J. T. Freeman; S. L. Taylor; S. A. Roberts (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Characterization of Fusarium mangiferae isolates from mango malformation disease in Southern Spain - M. Crespo; E. Arrebola; F. M. Cazorla; M. Maymon; S. Freeman; J. A. Torés; A. de Vicente (European Journal of Plant Pathology, 2014)

Joint effects between five identified risk variants, allergy, and autoimmune conditions on glioma risk - Mahboobeh Safaeian; Preetha Rajaraman; Patricia Hartge; Meredith Yeager; Martha Linet; Mary Ann Butler; Avima M. Ruder; Mark P. Purdue; Ann Hsing; Laura Beane-Freeman; Jane A. Hoppin; Demetrius Albanes; et al. (Cancer Causes & Control, 2013)

Rock lobster biology and ecology: contributions to understanding through the Leigh Marine Laboratory 1962–2012 - AB MacDiarmid; D Freeman; S Kelly (New Zealand Journal of Marine and Freshwater Research, 2013)
We review the contributions from research conducted through the Leigh Marine Laboratory (LML) since its establishment in 1962, to the understanding of the biology and ecology of the rock lobster, Jasus edwardsii. The number of publications (103 since 1978), their breadth of subject matter, and their frequency of citation indicate the influence of this research effort. The development of an underwater population sampling tool at the LML has been key to the research on lobster distribution, abundance, size structure and sex ratios. These, in turn, allowed significant insights into the impact of fishing on lobster populations, population recovery in marine reserves, the mating system of lobsters, and the cascading effects of lobster removal on reef communities. Other key research has focused on the planktonic larval and post‐larval stages. It is likely that J. edwardsii has received a greater level of ecological research effort through the LML than any other species. The location of the LML on a stretch of rocky coastline with year‐round easy access to the field, and the availability of a rebuilding population of J. edwardsii in an adjacent marine reserve, allowed coupled laboratory and field research to rapidly develop without the confounding effects of fishing. The LML is well placed to address outstanding questions about lobster biology and ecology, and to further contribute to the conservation and management of this important resource.

Genetic analysis of the near-infrared spectral phenome of a global Eucalyptus species - J. M. O’Reilly-Wapstra; J. S. Freeman; R. Barbour; R. E. Vaillancourt; B. M. Potts (Tree Genetics & Genomes, 2013)

A gastropod’s induced behavioral and morphological responses to invasive Carcinus maenas in Australia indicate a lack of novelty advantage - Aaren S. Freeman; Jeffrey T. Wright; Chad L. Hewitt; Marnie L. Campbell; Kaylene Szeto (Biological Invasions, 2013)

Matching and mismatching stable isotope (δ13C and δ15N) ratios in fin and muscle tissue among fish species: a critical review - Trevor J. Willis; Christopher J. Sweeting; Sarah J. Bury; Sean J. Handley; Julie C. S. Brown; Debbie J. Freeman; Dan G. Cairney; Michael J. Page (Marine Biology, 2013)

The effect of nicotine on sign-tracking and goal-tracking in a Pavlovian conditioned approach paradigm in rats - Matthew I. Palmatier; Kimberley R. Marks; Scott A. Jones; Kyle S. Freeman; Kevin M. Wissman; A. Brianna Sheppard (Psychopharmacology, 2013)

Eyeblink Conditioning in Healthy Adults: A Positron Emission Tomography Study - Krystal L. Parker; Nancy C. Andreasen; Dawei Liu; John H. Freeman; Laura L. Boles Ponto; Daniel S. O’Leary (The Cerebellum, 2012)

Genome-wide association study of glioma and meta-analysis - Preetha Rajaraman; Beatrice S. Melin; Zhaoming Wang; Roberta McKean-Cowdin; Dominique S. Michaud; Sophia S. Wang; Melissa Bondy; Richard Houlston; Robert B. Jenkins; Margaret Wrensch; Meredith Yeager; Anders Ahlbom; et al. (Human Genetics, 2012)

Comparative Evaluation of Mitral Valve Strain by Deformation Tracking in 3D-Echocardiography - S. Ben Zekry; G. Lawrie; S. Little; W. Zoghbi; J. Freeman; A. Jajoo; S. Jain; J. He; A. Martynenko; R. Azencott (Cardiovascular Engineering and Technology, 2012)

Reconciling the optimal and empirical approaches to modelling stomatal conductance - Belinda E. Medlyn; Remko A. Duursma; Derek Eamus; David S. Ellsworth; I. Colin Prentice; Craig V. M. Barton; Kristine Y. Crous; Paolo de Angelis; Michael Freeman; Lisa Wingate (Global Change Biology, 2012)

Cigarette smoking, alcohol intake, and thyroid cancer risk: a pooled analysis of five prospective studies in the United States - Cari M. Kitahara; Martha S. Linet; Laura E. Beane Freeman; David P. Check; Timothy R. Church; Yikyung Park; Mark P. Purdue; Catherine Schairer; Amy Berrington de González (Cancer Causes & Control, 2012)

Transcriptional signatures mediated by acetylation overlap with early-stage Alzheimer’s disease - J. Vadnal; S. Houston; S. Bhatta; E. Freeman; J. McDonough (Experimental Brain Research, 2012)

Comparative epidemiology of CTX-M-14 and CTX-M-15 producing Escherichia coli: Association with distinct demographic groups in the community in New Zealand - J. T. Freeman; D. A. Williamson; H. Heffernan; M. Smith; J. E. Bower; S. A. Roberts (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Evidence for scent marking in vervet monkeys? - N. J. Freeman; G. M. Pasternak; T. L. Rubi; L. Barrett; S. P. Henzi (Primates, 2012)

An Asian ambrosia beetle Euwallacea fornicatus and its novel symbiotic fungus Fusarium sp. pose a serious threat to the Israeli avocado industry - Z. Mendel; A. Protasov; M. Sharon; A. Zveibil; S. Ben Yehuda; K. O’Donnell; R. Rabaglia; M. Wysoki; S. Freeman (Phytoparasitica, 2012)

Incorporating Economic Models into Seasonal Pool Conservation Planning - Robert C. Freeman; Kathleen P. Bell; Aram J. K. Calhoun; Cynthia S. Loftin (Wetlands, 2012)

High rates of susceptibility to ceftazidime among globally prevalent CTX-M-producing Escherichia coli: potential clinical implications of the revised CLSI interpretive criteria - D. A. Williamson; S. A. Roberts; M. Smith; H. Heffernan; A. Tiong; C. Pope; J. T. Freeman (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

High synteny and colinearity among Eucalyptus genomes revealed by high-density comparative genetic mapping - Corey J. Hudson; Anand R. K. Kullan; Jules S. Freeman; Danielle A. Faria; Dario Grattapaglia; Andrzej Kilian; Alexander A. Myburg; Brad M. Potts; René E. Vaillancourt (Tree Genetics & Genomes, 2012)

Physical activity, diabetes, and thyroid cancer risk: a pooled analysis of five prospective studies - Cari M. Kitahara; Elizabeth A. Platz; Laura E. Beane Freeman; Amanda Black; Ann W. Hsing; Martha S. Linet; Yikyung Park; Catherine Schairer; Amy Berrington de González (Cancer Causes & Control, 2012)

The Use of Recreation Planning Tools in U.S. Forest Service NEPA Assessments - Lee K. Cerveny; Dale J. Blahna; Marc J. Stern; Michael J. Mortimer; S. Andrew Predmore; James Freeman (Environmental Management, 2011)

Quantitative trait loci for foliar terpenes in a global eucalypt species - Julianne M. O’Reilly-Wapstra; Jules S. Freeman; Noel W. Davies; René E. Vaillancourt; Hugh Fitzgerald; Brad M. Potts (Tree Genetics & Genomes, 2011)

An hTERT-immortalized human urothelial cell line that responds to anti-proliferative factor - Jayoung Kim; Mihee Ji; Joseph A. DiDonato; Raymond R. Rackley; Mei Kuang; Provash C. Sadhukhan; Joshua R. Mauney; Susan K. Keay; Michael R. Freeman; Louis S. Liou; Rosalyn M. Adam (In Vitro Cellular & Developmental Biology - Animal, 2011)

Molecular diagnosis of Myxobolus spirosulcatus associated with encephalomyelitis of cultured yellowtail, Seriola quinqueradiata Temminck & Schlegel - H Yokoyama; T Yanagida; M A Freeman; T Katagiri; A Hosokawa; M Endo; M Hirai; S Takagi (Journal of Fish Diseases, 2010)
Mass mortality of cultured yellowtail, Seriola quinqueradiata , has recently been reported from fish farms in western Japan. Previous studies revealed that diseased fish were characterized by encephalomyelitis and presporogonic stages of a myxosporean‐like parasite in the spinal cord. However, the parasite has remained unidentified because of the lack of mature stages being present. Thus, in the present study, analysis of the small subunit ribosomal DNA (18S rDNA) of the parasite as well as in situ hybridization (ISH) studies using histological sections of the infected tissue was conducted. The 18S rDNA of the myxosporean had higher sequence similarities with those of bile‐duct‐infecting myxosporeans rather than those infecting nervous tissues and was identified as Myxobolus spirosulcatus . The ISH using specific probes demonstrated that the DNA amplified was derived from the multinuclear organisms found in histological sections. A highly sensitive and specific PCR‐based assay for M. spirosulcatus was developed, which revealed a high prevalence of infection in cultured yellowtail that exhibited the clinical signs of encephalomyelitis.

Evaluating Theobroma grandiflorum for comparative genomic studies with Theobroma cacao - David N. Kuhn; Antonio Figueira; Uilson Lopes; Juan Carlos Motamayor; Alan W. Meerow; Kathleen Cariaga; Barbie Freeman; Donald S. Livingstone; Raymond J. Schnell (Tree Genetics & Genomes, 2010)

Body mass index, effect modifiers, and risk of pancreatic cancer: a pooled study of seven prospective cohorts - Li Jiao; Amy Berrington de Gonzalez; Patricia Hartge; Ruth M. Pfeiffer; Yikyung Park; D. Michal Freedman; Mitchell H. Gail; Michael C. R. Alavanja; Demetrius Albanes; Laura E. Beane Freeman; Wong-Ho Chow; Wen-Yi Huang; et al. (Cancer Causes & Control, 2010)

QTL influencing growth and wood properties in Eucalyptus globulus - Jules S. Freeman; Simon P. Whittock; Brad M. Potts; René E. Vaillancourt (Tree Genetics & Genomes, 2009)

Microbial activity and diversity during extreme freeze–thaw cycles in periglacial soils, 5400 m elevation, Cordillera Vilcanota, Perú - S. K. Schmidt; D. R. Nemergut; A. E. Miller; K. R. Freeman; A. J. King; A. Seimon (Extremophiles, 2009)

Soil CO 2 flux and photoautotrophic community composition in high‐elevation, ‘barren’ soil - Kristen R. Freeman; Monte Y. Pescador; Sasha C. Reed; Elizabeth K. Costello; Michael S. Robeson; Steven K. Schmidt (Environmental Microbiology, 2009)
Summary Soil‐dominated ecosystems, with little or no plant cover (i.e. deserts, polar regions, high‐elevation areas and zones of glacial retreat), are often described as ‘barren’, despite their potential to host photoautotrophic microbial communities. In high‐elevation, subnival zone soil (i.e. elevations higher than the zone of continuous vegetation), the structure and function of these photoautotrophic microbial communities remains essentially unknown. We measured soil CO 2 flux at three sites (above 3600 m) and used molecular techniques to determine the composition and distribution of soil photoautotrophs in the Colorado Front Range. Soil CO 2 flux data from 2002 and 2007 indicate that light‐driven CO 2 uptake occurred on most dates. A diverse community of Cyanobacteria , Chloroflexi and eukaryotic algae was present in the top 2 cm of the soil, whereas these clades were nearly absent in deeper soils (2–4 cm). Cyanobacterial communities were composed of lineages most closely related to Microcoleus vaginatus and Phormidium murrayi , eukaryotic photoautotrophs were dominated by green algae, and three novel clades of Chloroflexi were also abundant in the surface soil. During the light hours of the 2007 snow‐free measurement period, CO 2 uptake was conservatively estimated to be 23.7 g C m −2 season −1 . Our study reveals that photoautotrophic microbial communities play an important role in the biogeochemical cycling of subnival zone soil.

A decade of the Super Dual Auroral Radar Network (SuperDARN): scientific achievements, new techniques and future directions - G. Chisham; M. Lester; S. E. Milan; M. P. Freeman; W. A. Bristow; A. Grocott; K. A. McWilliams; J. M. Ruohoniemi; T. K. Yeoman; P. L. Dyson; R. A. Greenwald; T. Kikuchi; et al. (Surveys in Geophysics, 2007)

Elucidation of pectinolytic enzyme activities of a non-pathogenic watermelon pathogen mutant, Fusarium oxysporum f.sp. niveum M87 - P. Basaran; M. Ozcan; Y. Denisov; S. Freeman (Australasian Plant Pathology, 2007)

Hyperhydration prior to a simulated second day of the 3-day moderate intensity equestrian competition does not cause arterial hypoxemia in Thoroughbred horses - B. S. Tennent-Brown; T. E. Goetz; M. Manohar; A. S. Hassan; D. E. Freeman; J. S. Bundy; M. R. Evans (European Journal of Applied Physiology, 2006)

Identification ofTrichoderma biocontrol isolates to clades according to ap-PCR and ITS sequence analyses - M. Maymon; D. Minz; O. Barbul; A. Zveibil; Y. Elad; S. Freeman (Phytoparasitica, 2004)

A hyperparasitic microsporidian infecting the salmon louse, Lepeophtheirus salmonis : an rDNA‐based molecular phylogenetic study - M A Freeman; A S Bell; C Sommerville (Journal of Fish Diseases, 2003)
The sea louse, Lepeophtheirus salmonis , is an obligate ectoparasitic copepod that lives on the external surface of salmonid fish. It is the most common ectoparasite of marine cage‐reared salmonids, causing major economic loss to the aquaculture industry. During a sea louse monitoring programme, samples of L. salmonis were found to harbour an unreported microsporidian parasite. The microsporidian was observed in pre‐adult and adult stages of both male and female copepods, with a prevalence of up to 5%. Unfixed spores were slightly pyriform in shape measuring 2.34 μ m by 1.83 μ m (±0.01 μ m) and were not observed to be enclosed by a sporophorous vesicle. The microsporidian infection was observed in all areas of the copepods’ body, xenoma‐like cysts forming directly under the cuticle in the epidermal tissue layer. In the present study, rDNA (530f–580r) sequence data gathered from the unidentified microsporidian parasite isolated from infected sea lice were compared with equivalents available in the databases in an attempt to identify its systematic position. The microsporidian was found to group within the phylogenetic clade containing the family Enterocytozoonidae, being most similar to members of the intranuclear genus Nucleospora . This is the first report of a hyperparasitic microsporidian infecting a caligid copepod.

Flowering phenology and compensation for herbivory in Ipomopsis aggregata - Rachael S. Freeman; Alison K. Brody; Christopher D. Neefus (Oecologia, 2003)

Microsatellite primers indicate the presence of asexual populations ofVenturia inaequalis in coastal Israeli apple orchards - Eric W. A. Boehm; S. Freeman; E. Shabi; T. J. Michailides (Phytoparasitica, 2003)

Evidence that channel catfish, Ictalurus punctatus (Rafinesque), mortality is not linked to ingestion of the hepatotoxin microcystin‐LR - G S Snyder; A E Goodwin; D W Freeman (Journal of Fish Diseases, 2002)
Catfish farms located in the south‐eastern USA using brackish (3–5 g NaCl L −1 ) well water experience sporadic fish kills sometimes with high mortality. An investigation of three catastrophic losses occurring in this region identified no involvement of infectious diseases or traditional water quality problems, including oxygen, ammonia or nitrite. The high mortality and time course of the problem was indicative of exposure to a toxin. Attempts by other workers to explain the cause of this unique syndrome (high chloride associated toxicosis of catfish, HCTC), suggested that the losses might be because of microcystin‐producing blooms of Microcystis aeruginosa , but our investigations failed to support this conclusion . We found that (1) the liver histology of catfish experimentally exposed to pure microcystin‐LR is very different from that of catfish sampled during outbreaks of HCTC; (2) measurements of microcystin‐LR concentrations in the three cases were far lower than the concentration required to kill catfish by experimental immersion; (3) the HCTC toxin appears to have a short half‐life, whereas microcystin‐LR does not; (4) experimental gavage of catfish with massive amounts of microcystin‐LR does not cause the acute mortality typical of HCTC; (5) outbreaks of HCTC appear to be associated with heavy blooms of Anacystis marina , a halophytic cyanobacteria, not with blooms of M. aeruginosa .

Abstracts of presentations at the 22nd Congress of the Israeli Phytopathological Society February 12–13,2001 ARO, The Volcani Center, Bet Dagan, Israel - D. Shtienberg; M. Reuveni; N. Shegalov; D. Shegalov; D. Eshel; Ruth Ben-Arie; D. Prusky; Nadia Korolev; J. Katan; Talma Katan; A. Sharon; L. Oren; et al. (Phytoparasitica, 2001)

Survival of introduced Tuber melanosyorum at two sites in Israel as measured by occurrence of mycorrhizas - V. Kagan-Zur; S. Freeman; Y. Luzzati; Nurit Roth-Bejerano; E. Shabi (Plant and Soil, 2001)

Abstracts of Presentations at the 21st congress of the Israeli phytopathological society February 14–15, 2000 ARO, the Volcani Center, Bet Dagan, Israel - S. Droby; G. Kritzman; A. Gamliel; Miriam Austerweil; Yael Skutelski; I. Peretz-Alon; E. Becker; J. Katan; R. Cohen; M. Edelstein; Carmela Horev; Y. Burger; et al. (Phytoparasitica, 2000)

Abstracts of papers presented at the 15th conference of the weed science society of Israel - H. Eizenberg; Z. Tanaami; R. Jacobsohn; A. Lalazar; M. Hayut; M. Sibony; A. Tal; B. Rubin; M. Sibony; T. Yossef; D. Plakhine; Y. Kleifeld; et al. (Phytoparasitica, 1999)

Analysis of the effects of histaminergic compounds on experimental nociception and body temperature in mice - P. Freeman; S. Owen; G. Sturman <!-I (Inflammation Research, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Enzymic involvement in the biogeochemical responses of a Welsh peatland to a rainfall enhancement manipulation - C. Freeman; G. B. Nevison; S. Hughes; B. Reynolds; J. Hudson (Biology and Fertility of Soils, 1998)

Abstracts of Presentations at the 19th Congress of the Israeli Phytopathological Society - M. Raviv; I. Nir; Y. Pinkas; E. Shabi; S. Elisha; Marcell Maimon; Y. Szmulewich; S. Freeman; E. Shabi; Y. Nitzani; Talma Katan; Y. Luzzati; et al. (Phytoparasitica, 1998)

Survey of Grauer's Gorillas (Gorilla gorilla graueri) and Eastern Chimpanzees (Pan troglodytes schweinfurthi) in the Kahuzi-Biega National Park Lowland Sector and Adjacent Forest in Eastern Democratic Republic of Congo - Jefferson S. Hall; Lee J. T. White; Bila-Isia Inogwabini; Ilambu Omari; Hilary Simons Morland; Elizabeth A. Williamson; Kristin Saltonstall; Peter Walsh; Claude Sikubwabo; Dumbo Bonny; Kaleme Prince Kiswele; Amy Vedder; et al. (International Journal of Primatology, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

The 18th congress of the israeli phytopathological society - Y. Elad; D. Shtienberg; H. Vintal; Y. Cohen; Sonia Farkash; Zipora Reshit; A. Baider; Edna Levy; I. S. Ben-Ze’ev; Y. Nitzani; Frieda Kleitman; Talma Katan; et al. (Phytoparasitica, 1997)

Monitoring changes of ice streams using time series of satellite-altimetry-based digital terrain models - Ute C. Herzfeld; Craig S. Lingle; Cecily Freeman; Chris A. Higginson; Michael P. Lambert; Li-Her Lee; Vera A. Voronina (Mathematical Geosciences, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

s of papers presented at the 63rd annual PAA meeting - Jose L. Rueda; Donald Berrios; W. R. Amoros; H. A. Mendoza; Jose Gil Archuleta; Gene D. Easton; C. R. Brown; Doug Bruce; Elsa Camadro; S. J. Peloquin; J. R. Davis; W. B. Jones; et al. (American Journal of Potato Research, 1979)

Suberization and periderm development in Norchief and Red Pontiac potatoes - S. A. Ali; D. C. Nelson; T. P. Freeman (American Journal of Potato Research, 1975)

Neural dynamics under noise in the olfactory system - S. M. Ahn; Walter J. Freeman (Biological Cybernetics, 1975)

Physiological and storage problems number - H. S. Yohe; Wm. Stuart; C. O. Appleman; John Bushnell; Julian A. Dimock; J. T. Rosa; Earl S. Johnston; E. P. Miller; Freeman Weiss (American Journal of Potato Research, 1925)